2013
DOI: 10.1111/1462-2920.12266
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature adapted primitive Protochlamydia found in Acanthamoeba isolated from a hot spring can grow in immortalized human epithelial HEp‐2 cells

Abstract: To elucidate how ancient pathogenic chlamydiae could overcome temperature barriers to adapt to human cells, we characterized a primitive chlamydia found in HS-T3 amoebae (Acanthamoeba) isolated from a hot spring. Phylogenetic analysis revealed the primitive species to be Protochlamydia. In situ hybridization staining showed broad distribution into the amoebal cytoplasm, which was supported by transmission electron microscopic analysis showing typical chlamydial features, with inclusion bodies including both el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 38 publications
(57 reference statements)
2
23
0
Order By: Relevance
“…In fact, we have previously shown that environmental chlamydiae ( Protochlamydia R18, Parachlamydia Bn 9 ) failed to grow in the immortalized epithelial cell line, HEp-2, at 37°C [ 13 15 ]. However, in contrast to these findings, we have also found that an amoebal endosymbiont, Protochlamydia , found in HS-T3 Acanthamoeba isolated from a hot spring, successfully adapted to HEp-2 cells at 37°C with active replication [ 16 ]. More importantly, while the evolution of pathogenic chlamydiae has involved a decrease in genome size to approximately 1.0–1.2 Mb, which may be a strategy to evade the host immune network, resulting in a shift to parasitic energy and metabolic requirements [ 17 ], the genomes of representative environmental chlamydiae are not decreasing and have stabilized at 2.4–3.0 Mb [ 12 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, we have previously shown that environmental chlamydiae ( Protochlamydia R18, Parachlamydia Bn 9 ) failed to grow in the immortalized epithelial cell line, HEp-2, at 37°C [ 13 15 ]. However, in contrast to these findings, we have also found that an amoebal endosymbiont, Protochlamydia , found in HS-T3 Acanthamoeba isolated from a hot spring, successfully adapted to HEp-2 cells at 37°C with active replication [ 16 ]. More importantly, while the evolution of pathogenic chlamydiae has involved a decrease in genome size to approximately 1.0–1.2 Mb, which may be a strategy to evade the host immune network, resulting in a shift to parasitic energy and metabolic requirements [ 17 ], the genomes of representative environmental chlamydiae are not decreasing and have stabilized at 2.4–3.0 Mb [ 12 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…An aposymbiotic strain was established from S13WT by treatment with rifampicin (RFP; 64 mg ml 21 ), and designated S13RFP (Okude et al, 2012). Acanthamoeba strain HS-T3, persistently infected with endosymbiont Protochlamydia HS-T3, was originally isolated from a hot spring located in Kanagawa Prefecture, Japan (Sampo et al, 2014). We generated a reconstructed S13RFP symbiont strain containing Protochlamydia HS-T3, designated S13HS-T3, for use in this study.…”
Section: Resultsmentioning
confidence: 99%
“…With this in mind, we previously isolated several environmental Acanthamoeba strains infected with endosymbiotic bacteria from natural and built environments, including soil, hot spring water and hospital floors. These strains have proven useful as models for understanding host-parasite relationships Nakamura et al, 2010;Sampo et al, 2014;Fukumoto et al, 2016). Among them, soil-borne Acanthamoeba strain S13WT, harbouring environmental nonpathogenic chlamydial strain Neochlamydia S13, was of particular interest for several reasons .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, the amoebal cells were regularly collected to assess bacterial numbers using quantitative real-time PCR (qPCR), the AIU assay and DAPI staining, according to methods described previously [10, 15]. Meanwhile, the immortal human cell line, HEp-2, was also infected with the bacteria at a MOI of 1–5.…”
Section: Methodsmentioning
confidence: 99%